The British Labour Party. Its history, growth, policy and leaders. Ed. by H. Tracey. [With contribs of J.R. Clynes, J. Vernon Radcliffe, M. Phillips a.o. With a forew. by C.R. Attlee] (Caxton, 1948)
With bibliogr., ills, indices, prts and tabs.